Toward a General Conceptualization of Multi-Display Environments - Garcia-Sanjuan, Fernando; Jaen, Javier; Nacher, Vicente (Frontiers in ICT, 2016)
Combining multiple displays in the same environment enables more immersive and rich experiences in which visualization and interaction can be improved. Although much research has been done in the field of multi-display environments (MDEs) and previous studies have provided taxonomies to define them, these have usually consisted of partial descriptions. In this paper, we propose a general taxonomy that combines these partial descriptions and complements them with new evidences extracted from current practice. The main contribution of this paper is the summarization of the key dimensions that conform MDEs and a classification of previous studies to illustrate them.